THE TRANSLATIONAL POSSIBILITY OF TARGETING LncRNAs AS A THERAPEUTIC STRATEGY FOR IDIOPATHIC PULMONARY FIBROSIS - YADAV, RAKESH KUMAR; SHAH, SHYAM; SHRIVASTAVA, AMIT KUMAR; GAO, JIAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Idiopathic pulmonary fibrosis (IPF) is an interstitial lung disease (ILD). IPF causes stiffness in the lungs which makes it difficult to breathe and get oxygen to the bloodstream. IPF is a particularly severe form of lung fibrosis with no completely known etiology and a median survival of 2.5−3.5 years after diagnosis. The phenotypic changes in the lung fibroblasts are believed to contribute to the development of idiopathic pulmonary fibrosis. Long intergenic non-coding RNAs (LncRNAs) have been identified as novel regulators of gene expression and protein activity. In non-stimulated cells, it showed reduced proliferation and inflammation but no difference in the fibrotic response of IPF fibroblasts. These functional changes in non-stimulated cells were associated with changes in the expression of the histone marks, H3K4me1, H3K4me3, and H3K27ac indicating a possible involvement of epigenetics. Following activation with TGF-β1 and IL-1β, it demonstrated an increased fibrotic but reduced inflammatory response in IPF fibroblasts. No significant difference in proliferation following PDGF exposure was observed. The LncRNAs, LINC00960, and LINC01140 were upregulated in IPF fibroblasts. Knockdown studies showed that LINC00960 and LINC01140 were positive regulators of proliferation in both control and IPF fibroblasts but had no effect on the fibrotic response. Knockdown of LINC01140 but not LINC00960 increased the inflammatory response, which was greater in IPF compared to control fibroblasts. Overall, this review study tries to emphasize the role of LncRNAs as regulators of proliferation and inflammation in human lung fibroblast, a biomarker in IPF, and a novel treatment approach.